The efficacy of the school readiness initiative programme in the assessment of early childhood development learners in Buhera District - Manzunzu, Nomatter; Mupome, Nyaradzo Paula; Mwaruta, Fortunate (Papanda Publisher, 2024)
This study focused the efficacy of the School Readiness Initiative programme in the assessment of Early Childhood Development (ECD) learners in Buhera District. A qualitative case study was used to establish the effectiveness of the School Readiness Initiative on the assessment of Early Childhood Development learners. Ten teachers from different schools were purposively sampled. Questionnaires, interviews and observations were used to collect data from the participants. Data were presented in narratives and later analysed in themes. The results revealed that the School Readiness Initiative programme has positive effects in as far as Early Childhood Development learners` assessment is concerned. Some challenges in implementing the School Readiness Initiative programme in schools were poor internet connectivity, prolonged power cuts, and lack of expertise to use the Smart Tablet for Early Learning Assessment (STELA) tool on the part of the ECD teachers. The study therefore, recommended continual training of ECD teachers on various assessment techniques including the use of the STELA tool. It was also recommended that schools should have alternative sources of power such as solar energy.